Synthesis and Characterization of High Conductivity Polyaniline Prepared at Room Temperature - Budi, Setia; Puspa Rini, Eka; Paristiowati, Maria; Imaduddin, Agung; Syafei, Devi (Chemistry and Materials, 2022)
In this study, polyaniline was successfully synthesized using an oxidative polymerization method at room temperature. The polymerizations were carried out with and without stirring process under ultraviolet (UV) irradiation. The polyaniline was characterized by FTIR, XRD, SEM, SAA, and Four Point Probe. It is found that UV irradiation and stirring could increase the surface area and conductivity of polyaniline. The surface area obtained for stirred and unstirred polymerization were 37.9 m2/g and 29.0 m2/g, respectively. Moreover, conductivity values for stirred and unstirred polymerization were found as 1.22 S/cm and 1.08 S/cm respectively. This result shows that polyaniline synthesized by stirring treatment obtained uniform morphology, smaller size, greater crystallinity, higher BET surface area, and higher conductivity than that that of without stirring.